KEBIJAKAN LABELING TERHADAP IMPOR WINE DI PASAR UNI EROPA TAHUN 2010-2012 (STUDI KASUS: WINE AUSTRALIA) - Ulfa, Putri Nabillah; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes about how the impact of wine labeling policy reform by the European Union to Australian wine imports in the EU market in 2010 until 2012. This is done by European Union because Australian wine import in 2004, 2005 and 2006 increase in EU Market. Besides that, European Union wants to protect their wine by the reformation. In this research writer finds out that wine labeling policy reforms by European Union has influence to protect their domestic products from the Australian wine products. The new wine labeling rules impact on the decreasing Australian wine imported products.Keywords: Wine, Labeling, Reform, Import, European Union.